Technology of micro-cement injection of destroyed and fractured massif at orlovsky mine - Krupnik, L.; Shaposhnik, Yu.; Shaposhnik, S.; Konurin, A. (Розробка родовищ, 2017)
Purpose. Research into the method of strengthening destroyed and fractured rock massif by micro-cement injection during rock driving at Orlovsky mine of “Vostoktsvetmet” LLP. Findings. Massif strengthening method was studied. MasterRoc MP 650 micro-cement produced by BASF Construction Chemicals Ltd with addition of 1 – 2% of cement weight of Rheobuild 2000PF was used as cement slurry. The uniformity of the working contour in tunnel faces was observed after the third cycle of works on rocks injection. Unsafe working conditions for packer installation have been revealed. It was recommended to carry out pilot tests of tunneling technology in destroyed and fractured massif using the two-component organic-mineral resin “Blocksil” and long selfwedging packers with injection tubes. Originality. We established peculiarities of implementing technology of strengthening destroyed and fractured rock massif by micro-cement injection. Quantitative indicators of micro-cement content in the injected rock massif were identified.